2016
DOI: 10.1175/bams-d-13-00089.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aviation on Climate: FAA’s Aviation Climate Change Research Initiative (ACCRI) Phase II

Abstract: Current and future climate impacts of aviation emissions are quantified using a combination of atmospheric models, surface and satellite observations, and laboratory experiments. IMPACT OF AVIATION ON CLIMATEFAA's Aviation Climate Change Research Initiative (ACCRI) Phase II by Guy P. brasseur, Mohan GuPta, bruce e. anderson, sathya balasubraManian, steven barrett, david duda, GreGG FleMinG, Piers M. Forster, Jan FuGlestvedt, andrew GettelMan, ranGasayi n. halthore, s. daniel Jacob, Mark Z. Jacobson, areZoo kho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 74 publications
4
92
0
Order By: Relevance
“…We further derive SO 2 emissions by scaling the BC emissions with the ratio of the emission factors of the two species at each altitude level (see R13 for details) in all scenarios. This results in total aviation emissions of 0.168 Tg(SO 2 ) a −1 in 2000, which compares well with the ACCRI/AEDT value of 0.221 Tg(SO 2 ) a −1 in 2006 (Brasseur et al, 2015). We further assume that 2.2 % of the sulfur mass is emitted as primary SO 4 , based on Jurkat et al (2011).…”
Section: Model Setup Emission Inventories and Model Simulationssupporting
confidence: 66%
“…We further derive SO 2 emissions by scaling the BC emissions with the ratio of the emission factors of the two species at each altitude level (see R13 for details) in all scenarios. This results in total aviation emissions of 0.168 Tg(SO 2 ) a −1 in 2000, which compares well with the ACCRI/AEDT value of 0.221 Tg(SO 2 ) a −1 in 2006 (Brasseur et al, 2015). We further assume that 2.2 % of the sulfur mass is emitted as primary SO 4 , based on Jurkat et al (2011).…”
Section: Model Setup Emission Inventories and Model Simulationssupporting
confidence: 66%
“…The formation of contrails should increase the cloud fraction and its volume is, under our contrail parameterization, the product of flight distance and a cross section of 300 and 300 m. However, the uptake of background humidity upon the formation of contrails leads to a reduction of relative humidity of the grid cell.. Such dehydration process has been discussed in Brasseur et al (1998Brasseur et al ( , 2015, Sausen et al (2005), Lee et al (2009Lee et al ( , 2010 and Boucher et al (2013). Indeed, it is found that the relative/specific humidity at the cruise altitude is slightly reduced over Central Europe and eastern USA (not shown).…”
Section: Zonal Mean Perturbationsmentioning
confidence: 76%
“…The model is driven by air traffic waypoint data. Here, we use a global data set for the year 2006, including about 80 000 flights day −1 , as provided within the AC-CRI (Aviation Climate Change Research Initiative) project (Wilkerson et al, 2010;Brasseur et al, 2015). The fuel consumption and the corresponding water emissions from aircraft engines are available with these waypoint data.…”
Section: The Contrail Simulation Model Cocipmentioning
confidence: 99%
“…Nevertheless, the dehydration effects from contrails are not well known. Previous assessments of the climate impact of aviation (Schumann, 1994;Brasseur et al, 1998Brasseur et al, , 2015Penner et al, 1999;Sausen et al, 2005;Lee et al, 2009Lee et al, , 2010Boucher et al, 2013) discussed the dehydration effects from contrails qualitatively. Burkhardt and Kärcher (2011) were the first to quantify the dehydration effects within a global climate model.…”
Section: Introductionmentioning
confidence: 99%